(untitled) (Global Journal of Management and Business Research, 2020)
It is estimated that the current affordable housing deficit stands at 2 million houses with nearly 61% of urban households living in slums. This deficit continues to rise due to fundamental constraints on both the demand and supply side and is exacerbated by an urbanization rate of 4.2%, equivalent to 0.5 million new city dwellers every year. The study intended to examine how project management triple constraints and performance of affordable housing program in Kenya.